Comparison of Central Obesity with Overall Obesity in Predicting the Risk of Type 2 Diabetes Mellitus - Joshi, Bishal; Shrestha, Laxmi; Bhattarai, Kushal; Manandhar, Nilu; Mahotra, Narayan Bahadur (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Many studies have shown the association of waist circumference, waist hip ratio and body mass index with type 2 diabetes mellitus. Waist circumference and waist hip ratio have been used as measures of central obesity and body mass index has been used as a measure of general obesity. Objective of this study is to find out which type of obesity is better for prediction of risk of type 2 diabetes mellitus. MATERIAL AND METHODS:Total 100 participants with confirmed diagnosis of type 2 DM with age group 35-80 years were selected for the study. Anthropometric measurements like height, weight, waist circumference (WC) and hip circumference were measured and body mass index (BMI) and waist hip ratio (WHR) were calculated. Area under receiver operating characteristic (ROC) curve was used for correlating the parameters with type 2 diabetes mellitus in both male and female patients. RESULTS: Area under ROC curve, a measure of performance of the indices in predicting diabetes in total subjects, was found to be highest for waist hip ratio (0.840) followed by waist circumference (0.688) and BMI (0.608). Similarly, area under ROC curve was found maximum for waist hip ratio followed by waist circumference and body mass index in case of male and female patients. CONCLUSION: The present study concludes that anthropometric indicators of central obesity (WHR and WC) are more predictive for type 2 DM than anthropometric indicator of general obesity (BMI).